A laser composite plasma spark alloying method
Through the laser composite plasma EDM alloying method, the surface problems caused by no heat treatment after carburization are solved, and the surface hardness and wear resistance are significantly improved, the surface roughness is reduced, and the wear resistance is significantly improved.
Patent Information
- Application Number
- CN202111580323.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-12-22
AI Technical Summary
In the prior art, no heat treatment is performed after carburizing, resulting in carbide mesh cracks on the surface, uneven carbide thickness, and insufficient wear-resistant layer strength.
The laser composite plasma EDM alloying method is used. Surface laser treatment is performed after plasma EDM alloying. The laser beam is focused directly behind the electrode and the carburized layer is scanned laterally perpendicular to the alloying direction. The laser remelting depth is 0.05 to 0.50mm.
The surface hardness and wear resistance are significantly improved, the surface roughness is reduced, and a uniform carburized layer is achieved. The wear resistance is increased by about 35-40%, and can be increased by 80% when using modified electrodes.
Smart Images

Figure CN114318212B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser, electrophysical and electrochemical processing methods, and in particular relates to a laser composite plasma electric spark alloying method. Background Art
[0002] A method for hardening the surface of a steel part by electro-alloying is known [Patent UA103701C2: Method for hardening the surface of a steel part by heat treatment. Inventors: Martsinkovskiy VS, Tarelnik VB November 11, 2013]. The present invention provides a method for hardening the surface of a steel part by heat treatment. The method comprises electro-alloying, i.e. electro-alloying and ion nitriding of the heat-treated part, wherein the ion nitriding is performed before and after the electro-alloying. The ion nitriding time is to ensure that the alloying layer can be fully nitrided. The performance of the alloying layer, especially the wear resistance, can be improved by this method.
[0003] A method for smoothing and polishing surfaces by treating them with energetic radiation is known [Patent US7592563B2: Method for smoothing and polishing surfaces by treating them with energetic radiation. Inventors: K. Wissenbach, E. Willenborg, N.Pirch. C21D1 / 09.22.09.2009.]. The present invention relates to a method for smoothing and polishing surfaces using a high energy beam, in particular a laser beam. The method is divided into two stages. In the first stage, a specified energy beam is used to remelt the surface to be smoothed, using continuous radiation or pulse radiation with a pulse duration of ≥100 microseconds, and the remelting depth is 5 to 100 microns; in the second stage, the processing parameters of the first stage are used for polishing, and the polishing depth is greater than the roughness value of the smoothed surface. This method can be used to quickly and economically polish the surface of a three-dimensional body.
[0004] The method closest in technical essence (prototype) to the described method is a method for carburizing steel parts by electro-alloying [patent RU 2468899 C1: A method for carburizing steel parts by electro-alloying. Inventors: Martsinkovskiy VS, Tarelnik VB, Bratushchak MP B23Н9 / 00. 10.12.2012.]. According to the invention, during carburizing of steel parts, graphite is used as anode and steel parts are used as cathode, and electro-alloying of the surface of the parts is carried out in stages. At each subsequent stage, the discharge energy of the electro-alloying is gradually reduced, which can reduce the surface roughness of the steel parts while maintaining the surface quality.
[0005] A method of hardening the surface of steel parts by electro-etching alloying has the disadvantage of requiring two operations (electro-etching alloying and corresponding ion nitriding), which leads to an increase in the number of equipment, increased processing costs, and reduced productivity. At the same time, the micro-arcing action that occurs during the electro-etching alloying process causes metal spatter and increases the roughness of the machined surface.
[0006] A method for smoothing and polishing a surface by treatment with a high-energy beam has the disadvantage that only the roughness of the treated surface is improved without hardening it.
[0007] A method of carburizing steel parts by electro-etching alloying has the disadvantage that no heat treatment is performed after carburizing, which leads to the formation of carbide network cracks on the treated surface, uneven carbide thickness, and insufficient wear-resistant layer strength.
[0008] In view of the above technical problems, improvements need to be made. Summary of the invention
[0009] The present invention aims to provide a laser composite plasma spark surface alloying method. It solves the problems in the prior art that no heat treatment is performed after carburizing, resulting in the formation of carbide network cracks on the treated surface, uneven carbide thickness, insufficient wear-resistant layer strength, etc. Compared with the carburizing process, the present method can significantly improve the surface hardness and wear resistance, while reducing the surface roughness and uniform carburized layer.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is: a laser composite plasma spark alloying method, graphite is used as an anode and a steel part is used as a cathode; comprising the following steps:
[0011] Step 1, carburizing the steel parts by plasma spark alloying;
[0012] Step 2: Surface laser treatment after plasma spark alloying;
[0013] Step 3: When carburizing by plasma spark alloying, the laser beam is focused directly behind the electrode and the carburized layer is scanned transversely perpendicular to the alloying direction. The laser remelting depth is 0.05 to 0.50 mm.
[0014] As a preferred embodiment of the present invention, when carburizing is performed by plasma spark alloying, the laser beam is focused directly in front of the electrode and horizontally scanned perpendicular to the alloying direction, and the laser remelting depth is 0.05 to 0.50 mm.
[0015] As a preferred embodiment of the present invention, when plasma spark alloying is used for carburizing, the laser beam can be focused simultaneously before and after the electrode, and horizontal scanning is performed perpendicular to the alloying direction, and the laser remelting depth is 0.05 to 0.50 mm.
[0016] As a preferred solution of the present invention, laser remelting is performed after plasma spark alloying, and transverse scanning may or may not be performed.
[0017] As a preferred solution of the present invention, the overlap rate of laser scanning is 0-50%, and the distance between scanning tracks is 10-100% of the track width.
[0018] As a preferred embodiment of the present invention, the graphite electrode contains high-hardness wear-resistant particles with a size less than 100 μm, and the laser beam can be continuous or pulsed.
[0019] As a preferred embodiment of the present invention, when a continuous laser beam is used, the power range is 20-2000W; when a pulsed laser beam is used, the pulse frequency is 5Hz to 50kHz, and the power range is 20-2000W.
[0020] As a preferred solution of the present invention, alloy material electrodes can be used, in which case an intermetallic compound phase is formed in the alloyed region of the part.
[0021] As a preferred embodiment of the present invention, the plasma spark and laser treatment are carried out in a nitrogen or carbon dioxide gas atmosphere.
[0022] As a preferred embodiment of the present invention, a titanium alloy or aluminum alloy part can be used as the cathode.
[0023] The beneficial effects of the present invention are:
[0024] 1. The present invention obtains a 0.5 mm deep hardened layer on a metal substrate under specified processing conditions, including a remelting alloy zone (depth of 0.30-0.35 mm) and a solid phase hardened zone. In this case, the surface roughness of the processing is Ra 2.5-5.0 mm. According to the prototype method, by gradually reducing the processing energy and performing multiple passes of electro-etching alloying, a carburized layer with a depth of 0.30-0.35 mm and a surface roughness not exceeding Ra5.0 mm can be obtained.
[0025] 2. When the graphite electrode was used for electro-etching alloying according to the prototype method, the measured wear rate of the machined surface was 0.55 g / h; when the present method was used for alloying, the measured wear rate was 0.40 g / h; when the graphite electrode containing Al2O3 particulate additive was used, the measured wear rate was 0.30 g / h.
[0026] 3. Compared with the prototype method using the same electrode, the present invention uses a proposed laser composite plasma spark alloying method to improve the wear resistance by about 35-40%. When using a modified electrode, the wear resistance can be improved by 80%, while reducing the surface roughness.
[0027] This demonstrates its effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a principle diagram of a laser composite plasma spark alloying method of the present invention;
[0029] In the figure, 1- pulse generator 2- workpiece 3- electrode 4- vibrator 5- laser beam
[0030] Figure 2 The EILV-8 electrospark machining device used in the present invention is produced by Voroshilovgrad PTIMASh Company (Russia);
[0031] Figure 3 The MFSC1000W fiber laser used in the present invention is produced by Maxphotonics Co., Ltd (China);
[0032] Figure 4 This is a graph of the surface alloying of a 100×50 mm plate using a graphite electrode in the present invention;
[0033] Figure 5 This is the actual processing diagram when the scanning overlap rate of the focused laser beam of the present invention is about 20%
[0034] Figure 6 It is the organizational morphology of the remelting alloy zone (depth of 0.30-0.35 mm) and the solid phase hardening zone of the present invention;
[0035] In the figure, 6-metal substrate 7-remelting alloy zone 8-solid phase hardening zone
[0036] Figure 7 This is the effect of alloying a Ø50×20 mm35NiCrMoV12-5 steel cylindrical sample according to the present invention;
[0037] Figure 8 It is a structural schematic diagram of the test bench of the present invention.
[0038] In the figure, 9-sample 10-matched friction pair 11-load. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate unit, or it can be internally connected between two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0041] The present invention relates to a laser composite plasma spark alloying method, wherein graphite is used as an anode and a steel component is used as a cathode; the method comprises the following steps:
[0042] Step 1, carburizing the steel parts by plasma spark alloying;
[0043] Step 2: Surface laser treatment after plasma spark alloying;
[0044] Step 3: When carburizing by plasma spark alloying, the laser beam is focused directly behind the electrode and the carburized layer is scanned transversely perpendicular to the alloying direction. The laser remelting depth is 0.05 to 0.50 mm.
[0045] Under the specified processing conditions, a hardened layer with a depth of 0.5 mm was obtained on the metal base material, which contained a remelted alloy zone (depth of 0.30-0.35 mm) and a solid phase hardened zone. In this case, the surface roughness of the processing was Ra2.5-5.0 mm. According to the prototype method, by gradually reducing the processing energy and performing multi-pass electro-etching alloying, a carburized layer with a depth of 0.30-0.35 mm and a surface roughness not exceeding Ra5.0 mm can be obtained.
[0046] Among them, when carburizing is performed by plasma spark alloying, the laser beam can be focused directly in front of the electrode and scanned horizontally perpendicular to the alloying direction at the same time. The laser remelting depth is 0.05 to 0.50 mm.
[0047] Laser remelting is performed after plasma spark alloying, and laser scanning may or may not be performed.
[0048] The overlap rate of the laser scan is 0-50%, and the distance between the scanned tracks is 10-100% of the track width.
[0049] The graphite electrode contains high-hardness wear-resistant particles with a size less than 100 μm, and the laser beam can be either continuous or pulsed.
[0050] When using a continuous laser beam, the power range is 20-2000W; when using a pulsed laser beam, the pulse frequency is 5Hz to 50kHz and the power range is 20-2000W.
[0051] When alloy material electrodes are used, intermetallic compound phases can be formed in the alloying area of the part.
[0052] Plasma spark and laser processing are carried out in a nitrogen or carbon dioxide gas atmosphere.
[0053] Titanium alloy or aluminum alloy parts can be used as cathodes.
[0054] Compared with the prototype method using the same electrode, the laser composite plasma spark alloying method of the present invention can improve the wear resistance by about 35-40%. When using the modified electrode, the wear resistance can be improved by 80%, while reducing the surface roughness, which shows its effectiveness.
[0055] The essence of the present invention is illustrated by the accompanying drawings: Figure 1 It is a schematic diagram of a laser composite plasma spark alloying method of the present invention. The cathode of the pulse generator 1 is connected to the metal workpiece 2, and the anode is connected to the electrode 3 through the vibrator 4, and the electrode 3 is fixed in the electrode chuck of the vibrator 4; the laser beam 5 is focused on the workpiece 2 behind the electrode 3 and scanned horizontally perpendicular to the alloying direction. During alloying, the electrode moves along the surface at a speed of 0.1m / min to 1m / min. Due to the action of the vibrator 4, the electrode 3 vibrates perpendicularly to the surface to be hardened, resulting in plasma spark discharge between the workpiece 2 and the electrode 3.
[0056] The results obtained according to the proposed method are as follows.
[0057] The electrode 3 is fixed in the electrode chuck of the vibrator 4, and is made of pure graphite or graphite containing high-hardness wear-resistant particles (e.g., Al2O3, TiO2, WВ, W2Si3, etc.) with a size less than 100μm. Under the action of the pulse current, plasma spark discharge is generated between the anode (electrode 3) and the cathode (workpiece 2), and a liquid metal molten pool (depth of about 0.50mm) is formed on the surface of the workpiece 2, and the material of the electrode 3 is transferred to the surface layer of the workpiece 2. In this case, the graphite in the electrode 3 promotes the carburization of the surface layer of the workpiece 2, and the wear-resistant particles therein are also transferred to the surface layer of the workpiece 2 during the alloying process, thereby improving the wear resistance of the workpiece 2.
[0058] In order to reduce the roughness and perform heat treatment (e.g. quenching) on the alloyed surface, the laser beam 5 is focused behind the electrode 3 and scanned transversely in the width direction of the processing path (i.e. the processing width of the electrode 3), and the laser remelting depth is 0.05-0.50 mm. The type of heat treatment is changed by changing the thermal cycle. The transverse scanning of the focused laser beam 5 can be performed directly in front of the electrode 3 or simultaneously in front of and behind the electrode 3 during the alloying process of the workpiece 2. In this case, the normalizing or tempering process is performed simultaneously with the alloying.
[0059] In order to obtain a composite layer composed of an alloy phase on the processed surface, the electrode 3 is made of a metal that can form an intermetallic compound phase during the alloying process (for example, Ti or Al is used when processing the steel surface, steel or Al is used when processing the titanium alloy surface, and steel or Ti is used in aluminum alloy processing). In this way, hard and wear-resistant intermetallic compounds such as TiFe, FeAl and other compounds can be formed during the alloying process. The alloying using laser composite plasma electric spark is carried out in a nitrogen or carbon dioxide protective gas. In this atmosphere, the alloyed surface easily forms new compounds with these gases (for example, when titanium alloy is processed in nitrogen, titanium nitride is formed).
[0060] Figure 2 The EILV-8 electrospark machining device used in the present invention is produced by Voroshilovgrad PTIMASh Company (Russia), Figure 3 The MFSC1000W fiber laser used in the present invention is produced by Maxphotonics Co., Ltd. (China). The laser composite plasma spark alloying experiment was carried out using these two devices to verify the effectiveness of the proposed method.
[0061] The experiment was conducted in two stages. In the first stage, the plate samples were alloyed according to the prototype method and the proposed method. The sample material was 38ХН3МФА (35NiCrMoV12-5) steel with a size of 100×50×20mm. The electrode used was a graphite electrode and the EDM energy was 7.0J. The processing was carried out in nitrogen protection with a nitrogen flow rate of 8-10l / min.
[0062] According to the proposed method ( Figure 4 ), laser scanning was performed after electro-etching alloying. The laser power was 400 W (the diameter of the focused spot was 0.1 mm), the overlap rate was 20% (Figure 5), and the laser scanning speed was 50 m / h. Finally, a hardened layer with a depth of 0.5 mm was obtained on the metal substrate 6, including a remelted alloy zone 7 (depth of 0.30-0.35 mm) and a solid phase hardened zone 8 (such as Figure 6 ), at this time the roughness of the machined surface is Ra 2.5-5.0mm.
[0063] According to the prototype method, multi-pass electro-etching alloying was carried out by gradually reducing the processing energy, and finally a carburized layer with a depth of 0.30-0.35 mm and a surface roughness of Ra5.0mm was obtained.
[0064] In the second stage, the cylindrical samples were alloyed according to the prototype method and the proposed method ( Figure 7 ). The sample material was 38ХН3МФА (35NiCrMoV12-5), with a size of Ø50×20 mm, and alloying was performed along the Ø50 mm cylindrical surface. According to the prototype method, alloying was performed three times, each time with a 50% reduction in energy; according to the proposed method, only one alloying was performed. The maximum energy of the plasma spark treatment was 6.8 J, and the laser radiation power was 300 W (focused spot diameter was about 0.1 mm). The vibrator electrode chuck was fixed to the machine tool chuck, and the sample rotated continuously at a speed of 4-6 rpm. The processing width was about 3 mm, the laser beam lateral scanning frequency was 30 Hz, and the flow rate of the protective gas nitrogen was 8-10 l / min.
[0065] After alloying, the wear resistance of the samples was tested on a test bench made on a lathe (Figure 8). For this purpose, the alloyed sample 9 was fixed on the three-jaw chuck of the lathe, and a matching friction pair 10 (material - T15K6 (79% WC+15% TiC+6% Co)) with a constant load 11 was installed on top of the sample. 2 ) under a load of 500 mm / s, the sample 9 was rotated at a linear speed of 500 mm / s and subjected to a dry friction test for one hour with the matching friction pair 10. The wear resistance was evaluated by the wear rate obtained from the test of the alloyed sample 9 (unit: g / h), and the wear rate was the average of three measurements.
[0066] The wear rate measured by the prototype method for electro-etching alloying with graphite electrodes was 0.55 g / h. The wear rate measured by the proposed method for alloying was 0.40 g / h; and the wear rate measured by the graphite electrode containing Al2O3 microparticle additives was 0.30 g / h.
[0067] Therefore, the proposed laser hybrid plasma spark alloying method can improve the wear resistance by about 35-40% compared with the prototype method using the same electrode; in the case of using the modified electrode, the wear resistance can be improved by 80% while reducing the surface roughness, which shows its effectiveness.
[0068] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art. The general principles defined in this invention may be implemented in other embodiments without departing from the spirit or scope of the invention; therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A laser composite plasma spark alloying method, graphite is used as anode and steel parts are used as cathode; characterized in that: The following steps are involved: Step 1, carburizing the steel parts by plasma spark alloying; Step 2: Surface laser treatment after plasma spark alloying; Step 3, when carburizing by plasma spark alloying, the laser beam is focused directly behind the electrode and the carburized layer is scanned transversely perpendicular to the alloying direction, and the laser remelting depth is 0.05 to 0.50 mm; When using a continuous laser beam, the power range is 20-2000W; when using a pulsed laser beam, the pulse frequency is 5Hz to 50kHz, and the power range is 20-2000W; The cathode of the pulse generator is connected to the metal workpiece, and the anode is connected to the electrode through a vibrator, and the electrode is fixed in the electrode chuck of the vibrator; the laser beam is focused on the workpiece behind the electrode and scanned transversely perpendicular to the alloying direction; during alloying, the electrode moves along the surface at a speed of 0.1m / min to 1m / min; due to the action of the vibrator, the electrode vibrates perpendicularly to the surface to be hardened, resulting in plasma spark discharge between the workpiece and the electrode; The electrode is fixed in the electrode chuck of the vibrator, which is made of pure graphite or graphite containing high-hardness wear-resistant particles with a size of less than 100μm; under the action of pulse current, plasma spark discharge is generated between the electrode and the workpiece, and a liquid metal molten pool is formed on the surface of the workpiece. At the same time, the material of the electrode is transferred to the surface layer of the workpiece. The graphite in the electrode promotes carburization of the surface layer of the workpiece, and the wear-resistant particles therein are also transferred to the surface layer of the workpiece during the alloying process, thereby improving the wear resistance of the workpiece.
2. The laser composite plasma spark alloying method according to claim 1, characterized in that: When carburizing by plasma spark alloying, the laser beam is focused directly in front of the electrode and the carburized layer is scanned transversely perpendicular to the alloying direction. The laser remelting depth is 0.05 to 0.50 mm.
3. The laser composite plasma spark alloying method according to claim 1, characterized in that: When using plasma spark alloying for carburizing, the laser beam is focused simultaneously before and after the electrode and scanned transversely perpendicular to the alloying direction. The laser remelting depth is 0.05 to 0.50 mm.
4. The laser composite plasma spark alloying method according to claim 1, characterized in that: The overlap rate of the laser scan is 0-50%, and the distance between the scanned tracks is 10-100% of the track width.
5. The laser surface plasma spark alloying method according to claim 1, characterized in that: The graphite electrode contains high hardness and wear-resistant particles with a size less than 100μm, and the laser beam is continuous or pulsed.
6. The laser composite plasma spark alloying method according to claim 1, characterized in that: When alloy material electrodes are used, an intermetallic compound phase is formed in the alloyed area of the part.
7. The laser composite plasma spark alloying method according to claim 1, characterized in that: Plasma spark and laser processing are carried out in a nitrogen or carbon dioxide gas atmosphere.
8. The laser composite plasma spark alloying method according to claim 1, characterized in that: Use titanium alloy or aluminum alloy parts as cathodes.
Citation Information
Patent Citations
Method for strengthening surface of steel parts being subject to thermal treatment (embodiments)
UA103701C2
Laser-chemical combined infiltration process for low-alloy steel die
CN105331986A
Mixed powder electric spark surface strengthening medium powder
CN109338361A